Outcomes and Prognostic Factors in Radioiodine Refractory Differentiated Thyroid Carcinomas. (16th December 2015) - Wassermann, Johanna; Bernier, Marie‐Odile; Spano, Jean‐Philippe; Lepoutre‐Lussey, Charlotte; Buffet, Camille; Simon, Jean‐Marc; Ménégaux, Fabrice; Tissier, Frédérique; Leban, Monique; Leenhardt, Laurence
Abstract : Background: Outcomes vary among patients with radioiodine refractory (RR) differentiated thyroid cancer (DTC). The prognostic factors for survival are not well‐known, resulting in difficulty in selecting patients for new targeted therapies. We assessed overall survival (OS) and cancer‐specific survival (CSS) from RR‐DTC to identify prognostic factors associated with survival. Patients and Methods: The data on all cases of metastatic RR‐DTC treated in our center from 1990 to 2011 were retrospectively reviewed. Survival was estimated using the Kaplan‐Meier method; associated prognostic factors were assessed using Cox's model. Results: Of 153 cases of metastatic DTC, 59% ( n = 91) met a criterion for RR: that is, 60% ( n = 55) had at least 1 metastasis without 131 I uptake; 21% ( n = 19) had progressive disease (PD) despite 131 I; 19% ( n = 17) had persistent disease despite a cumulative activity of 131 I of ≥600 mCi. After the diagnosis of RR, median OS was 8.9 years (95% confidence interval [CI]: 5.4‐NR); median CSS was 9.6 years (95% CI: 6.01‐NR). In multivariate analyses, PD despite 131 I as a criterion for RR disease and the time from initial diagnosis of DTC to diagnosis of RR <3 years were the only independent prognostic factors for poor OS and CSS. Thyroglobulin doubling time (Tg‐DT) was assessed in 31 of 91 cases. Among the 11 patients with Tg‐DT for <1 year or undetectable Tg, 6 deaths occurred, whereas only 3 died of 20 patients with Tg‐DT >1 year or negative Tg‐DT. Conclusion: The identification of prognostic factors for decreased survival in RR‐DTC may improve the selection of patients for targeted agents. Implications for Practice: This study shows a great heterogeneity in terms of prognosis in radioiodine refractory differentiated thyroid carcinoma. Poorer prognosis is observed in patients with tumor progression or with a diagnosis of radioiodine resistance within 3 years after the initial diagnosis of thyroid cancer. Those findings could lead to improvements in the selection of patients for targeted therapies. Abstract : This study assessed overall survival (OS) and cancer‐specific survival (CSS) from radioiodine refractory (RR)‐differentiated thyroid cancer (DTC) to identify survival prognostic factors to facilitate selecting patients for new targeted therapies. In multivariate analyses, the only independent prognostic factors for poor OS and CSS were progressive disease despite 131 I as a criterion for RR disease and the time from initial diagnosis of DTC to diagnosis of RR <3 years.